DIALEKTIKA RELASIONAL PASANGAN ANTAR NEGARA: STUDI KASUS PADA PASANGAN BELGIA - INDONESIA - Teguh, Monika; Swastika, Gabriela Laras Dewi; Gozali, Citta Catherine (Jurnal Spektrum Komunikasi, 2025)
A relationship cannot be limited by territorial or cultural boundaries. However, it must be recognised that the challenges in establishing intercultural relationships are also great, especially in phenomena such as COVID-19. The initial tension in relational dialectics is mostly triggered by changes in situations that become "out of normal" or unusual, because society needs to adapt again. One of them was experienced by an interstate couple domiciled in Indonesia and Belgium. Based on this phenomenon, this research was aimed to discuss how the relational dialectic of interstate pairs occurred. The purpose of this study is to find out the strategies of inter-country couples with dialectics in their relationships to maintain intimacy, even in the midst of restrictions. The research method used is descriptive qualitative, with data collection methods in the form of interviews. The results of the study show that the interstate pair devised a strategy so that the three main tensions, autonomy-connection, openness-non-disclosure, and predictability-newness can still be passed smoothly. Relational dialectics have already led to the stage of co-creating. Co-creation needs to be done to redefine the kind of relationship they want, as well as to develop a joint mission for the future.